2019
DOI: 10.1093/molbev/msz152
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of Sites under Immune Selection Shapes Epstein–Barr Virus Population Structure

Abstract: Epstein–Barr virus (EBV) is one of the most common viral infections in humans and persists within its host for life. EBV therefore represents an extremely successful virus that has evolved complex strategies to evade the host’s innate and adaptive immune response during both initial and persistent stages of infection. Here, we conducted a comparative genomics analysis on 223 whole genome sequences of worldwide EBV strains. We recover extensive genome-wide linkage disequilibrium (LD) despite pervasive genetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 45 publications
5
31
1
Order By: Relevance
“…Conversely, despite abundant recombination, EBV shows extensive genome-wide LD [85]. Because sites in LD are enriched in EBV genes that encode immunogenic proteins, Wegner and coworkers suggested that viral population structure is determined by local adaptation to human populations [85]. In summary, these data suggest that, although a wider sampling of HCMV diversity may in the future reveal some level of geographic clustering, most HCMV stains derive from a highly recombining panmictic population distributed worldwide.…”
Section: High Population-level Diversity Of Circulating Hcmv Strainsmentioning
confidence: 97%
See 3 more Smart Citations
“…Conversely, despite abundant recombination, EBV shows extensive genome-wide LD [85]. Because sites in LD are enriched in EBV genes that encode immunogenic proteins, Wegner and coworkers suggested that viral population structure is determined by local adaptation to human populations [85]. In summary, these data suggest that, although a wider sampling of HCMV diversity may in the future reveal some level of geographic clustering, most HCMV stains derive from a highly recombining panmictic population distributed worldwide.…”
Section: High Population-level Diversity Of Circulating Hcmv Strainsmentioning
confidence: 97%
“…Another notable difference among human herpesviruses is the degree of geographic structuring of viral populations. At one extreme stand VZV and EBV, which display a clear spatial distribution of genetic diversity [82][83][84][85]. For instance, VZV clades 1, 3, and 6 are mainly transmitted in Europe, North America, and Australia, whereas clade 2 is primarily Asian [83].…”
Section: High Population-level Diversity Of Circulating Hcmv Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another group investigated the co-evolution of worldwide EBV strains [34] and found extensive linkage disequilibrium (LD) throughout EBV genomes. Furthermore, they observed that genes in strong LD were enriched in immunogenic genes, suggesting adaptive immune selection and epistasis.…”
Section: Introductionmentioning
confidence: 99%